The Benefits and Costs of Cross-listing in the United States (2009)
Introduction. I. A Primer on American Depositary Receipts. II. The share price and cost of capital impact of cross-listing in the U.S.: Miller (1999). III. The effect of cross-listing on the information environment of the firm: Lang and Miller (2003). IV. The impact of cross-listing on CEO turnover: Lel and Miller (2008). V. Regulatory responses to firm's cross-listing decisions: Fernandez, Lel and Miller (2008). VI. Conclusions. References.